Young carers of stroke survivors - Cameron, Trudi M. (2018)
The UK has been at the forefront of young carer research internationally, creating a sound evidence base, influencing policy and developing support for young carers. Studies have consistently found young carers can gain positive attributes and skills from their caring role but that is not always the case. Where there are unmet needs, young carers can experience detriment to their health, well-being and future life chances. Some of the detrimental causes are condition-specific.